Here, is a positive integer. Find .
Note : Please refrain from using Wolfram Alpha or similar software to solve this problem.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Longish solution, can't seem to find a better one.
( 1 + x ) 2 0 = 1 + ( 1 2 0 ) x + ( 2 2 0 ) x 2 + . . . + ( 1 9 2 0 ) x 1 9 + x 2 0
( 1 + ω x ) 2 0 = 1 + ( 1 2 0 ) ω x + ( 2 2 0 ) ω 2 x 2 + . . . + ( 1 9 2 0 ) ( ω 1 9 ) x 1 9 + ω 2 0 x 2 0
( 1 + ω 2 x ) 2 0 = 1 + ( 1 2 0 ) ω 2 x + ( 2 2 0 ) ( ω 2 ) 2 x 2 + . . . + ( 1 9 2 0 ) ( ω 2 ) 1 9 x 1 9 + ( ω 2 ) 2 0 x 2 0
Where ω , ω 2 are the complex cube roots of unity.Adding all three we get,
( 1 + x ) 2 0 + ( 1 + ω x ) 2 0 + ( 1 + ω 2 x ) 2 0 = 3 ( 3 2 0 ) x 3 + 3 ( 6 2 0 ) x 6 + . . . + 3 ( 1 8 2 0 ) x 1 8
Since 1 n + ω n + ( ω 2 ) n = 0 if 3 ∣ n and 1 n + ω n + ( ω 2 ) n = 3 if 3 ∣ n
Differentiating w.r.t. x
2 0 ( ( 1 + x ) 1 9 + ω ( 1 + ω x ) 1 9 + ω 2 ( 1 + ω 2 x ) 1 9 ) = 3 ( 3 ( 3 2 0 ) x 2 + 6 ( 6 2 0 ) x 5 + . . . + 1 8 ( 1 8 2 0 ) x 1 7 )
Again Differentiating w.r.t. x .
2 0 ∗ 1 9 ( ( 1 + x ) 1 8 + ω 2 ( 1 + ω x ) 1 8 + ω ( 1 + ω 2 x ) 1 8 ) = 3 ( 3 ∗ 2 ( 3 2 0 ) x + 6 ∗ 5 ( 6 2 0 ) x 4 + . . . + 1 8 ∗ 1 7 ( 1 8 2 0 ) x 1 6 )
Adding both the above equations and putting x = 1 , we have,
2 0 ( ( 2 ) 1 9 + ω ( 1 + ω ) 1 9 + ω 2 ( 1 + ω 2 ) 1 9 ) + 2 0 ∗ 1 9 ( ( 2 ) 1 8 + ω 2 ( 1 + ω ) 1 8 + ω ( 1 + ω 2 ) 1 8 ) = 3 ( 3 ( 3 2 0 ) + 6 ( 6 2 0 ) + . . . + 1 8 ( 1 8 2 0 ) + 3 ∗ 2 ( 3 2 0 ) + 6 ∗ 5 ( 6 2 0 ) + . . . + 1 8 ∗ 1 7 ( 1 8 2 0 ) )
Since 1 + ω 2 = − ω and 1 + ω = − ω 2
⇒ 2 0 ( ( 2 ) 1 9 + ω ( − ω 2 ) 1 9 + ω 2 ( − ω ) 1 9 ) + 2 0 ∗ 1 9 ( ( 2 ) 1 8 + ω 2 ( − ω 2 ) 1 8 + ω ( − ω ) 1 8 ) = 3 ( 3 2 ( 3 2 0 ) + 6 2 ( 6 2 0 ) + . . . + 1 8 2 ( 1 8 2 0 ) )
Since ( − ω ) 6 n = ( − ω ) 6 n = 1 , we have
⇒ 2 0 ( ( 2 ) 1 9 + ω ( − ω 2 ) + ω 2 ( − ω ) ) + 2 0 ∗ 1 9 ( ( 2 ) 1 8 + ω 2 + ω ) = 3 ( 3 2 ( 3 2 0 ) + 6 2 ( 6 2 0 ) + . . . + 1 8 2 ( 1 8 2 0 ) )
And ω + ω 2 = − 1
⇒ 2 0 ( ( 2 ) 1 9 + ( − 1 ) + ( − 1 ) ) + 2 0 ∗ 1 9 ( ( 2 ) 1 8 + ( − 1 ) ) = 3 ( 3 2 ( 3 2 0 ) + 6 2 ( 6 2 0 ) + . . . + 1 8 2 ( 1 8 2 0 ) )
⇒ 2 0 ( ( 2 ) 1 9 − 2 ) + 2 0 ∗ 1 9 ( ( 2 ) 1 8 − 1 ) ) = 3 ( 3 2 ( 3 2 0 ) + 6 2 ( 6 2 0 ) + . . . + 1 8 2 ( 1 8 2 0 ) )
⇒ 4 0 ( ( 2 ) 1 8 − 1 ) + 3 8 0 ( ( 2 ) 1 8 − 1 ) = 3 ( 3 2 ( 3 2 0 ) + 6 2 ( 6 2 0 ) + . . . + 1 8 2 ( 1 8 2 0 ) )
⇒ 4 2 0 ( ( 2 ) 1 8 − 1 ) = 3 ( 3 2 ( 3 2 0 ) + 6 2 ( 6 2 0 ) + . . . + 1 8 2 ( 1 8 2 0 ) )
⇒ 1 4 0 ( ( 2 ) 1 8 − 1 ) = 3 2 ( 3 2 0 ) + 6 2 ( 6 2 0 ) + . . . + 1 8 2 ( 1 8 2 0 ) .
Therefore k = 1 4 0